Examining the Nelson-Siegel Class of Term Structure Models - Michiel De Pooter (Tinbergen Institute, 2007)
In this paper I examine various extensions of the Nelson and Siegel (1987) model with the purpose of fitting and forecasting the term structure of interest rates. As expected, I find that using more flexible models leads to a better in-sample fit of the term structure. However, I show that the out-of-sample predictability improves as well. The four-factor model, which adds a second slope factor to the three-factor Nelson-Siegel model, forecasts particularly well. Especially with a one-step state-space estimation approach the four-factor model produces accurate forecasts and outperforms competitor models across maturities and forecast horizons. Subsample analysis shows that this outperformance is also consistent over time.
Keywords: E4; C5; C32; 330; Term structure of interest rates; Nelson-Siegel; Svensson; Forecasting; State-space model; Zinsstruktur; Zustandsraummodell; Prognoseverfahren; Theorie